Primary lung carcinoid, a rare cause of paraparesis: report of a case and review of the literature - Visouli, Aikaterini N. (Pioneer Bioscience Publishing Company, 2012)
Carcinoids are neuroendocrine tumors mainly involving the gastrointestinal tract, lungs and bronchi. They were considered benign with slow growth, but they can be malignant in a substantial percentage of patients (metastasizing to liver, bones, skin, etc). Endocrine activity results in carcinoid syndrome. Proximal myopathy has been reported in 7% of patients with carcinoid syndrome. Bronchopulmonary and thymic carcinoids producing adrenocorticotropic hormone can cause Cushing’s syndrome, a main feature of which is myopathy. There are a few reports of carcinoids associated with paraneoplastic neurological syndromes, including neuropathy. We hereby present an extremely rare case of a primary lung carcinoid presented with paraparesis due to polyneuropathy, and review the relevant literature. To the best of our knowledge there is no similar previous report. Complete resolution of paraparesis after excision of the lung carcinoid suggests paraneoplastic neurological syndrome.